Spiral Progression Approach, Digital Literacy and Competency of Teachers: Basis for Learning Activity Guides - Calzado, Jeanette; Abo, Christine (Journal of Interdisciplinary Perspectives, 2025)
The K–12 curriculum adopted spiral progression and rapid digitalization of education, which exposed essential gaps in how science teachers integrated technology into their teaching framework. The study addressed the absence of empirical evidence about spiral progression implementation, digital literacy, and teacher competence to develop Learning Activity Guides. A descriptive-correlational research design included surveys of 23 junior high school science teachers and 45 Grade 10 students at Esperanza National High School to examine spiral progression implementation, digital practices, and teaching competencies through Likert-scale questionnaires, classroom observations, and self-evaluations. The mean and standard deviation results demonstrated that teachers strongly followed vertical and horizontal curriculum articulation principles and showed high confidence in their digital tool usage. Pearson’s r analysis showed that spiral progression implementation had a significant positive relationship with teacher competence (r=.54, p=.001) and digital literacy had a significant positive relationship with competence (r=.66, p=.022). The research results directly shaped the development of Learning Activity Guides, which linked spiral progression principles to technology-enhanced teaching methods. At the same time, administrators received proof to support professional development programs that connect digital skills to curriculum implementation methods. Future research may investigate student achievement outcomes while studying the qualitative aspects of teachers' technology integration experiences.